2015
DOI: 10.1088/1741-2560/12/6/066028
|View full text |Cite
|
Sign up to set email alerts
|

EEG-based decoding of error-related brain activity in a real-world driving task

Abstract: Abstract.Objectives. Recent studies have started to explore the implementation of braincomputer interfaces (BCI) as part of driving assistant systems. The current study presents an EEG-based BCI that decodes error-related brain activity. Such information can be used, e.g., to predict driver's intended turning direction before reaching road intersections. Approach. We executed experiments in a car simulator (N = 22) and a real car (N = 8). While subject was driving, a directional cue was shown before reaching a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
72
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(74 citation statements)
references
References 30 publications
2
72
0
Order By: Relevance
“…ErrPs have been used in brain-computer interfaces and HRI tasks for performing binary classification, correcting classification errors, and controlling various robot platforms [46,49,41,22,11,29,21,37,38,53,45]. Nevertheless, most ErrP studies are performed in controlled scenarios because EEG signals have low signalto-noise ratios that make real-time classification challenging [40,6,7,31,34,48].…”
Section: A Eeg-based Methods For Human-robot Interactionmentioning
confidence: 99%
“…ErrPs have been used in brain-computer interfaces and HRI tasks for performing binary classification, correcting classification errors, and controlling various robot platforms [46,49,41,22,11,29,21,37,38,53,45]. Nevertheless, most ErrP studies are performed in controlled scenarios because EEG signals have low signalto-noise ratios that make real-time classification challenging [40,6,7,31,34,48].…”
Section: A Eeg-based Methods For Human-robot Interactionmentioning
confidence: 99%
“…3,4 . Along this line, the possibility of decoding brain activity, measured with electroencephalography (EEG), to improve driving assistance systems has recently attracted considerable interest 11,13,14,29 . In this approach, the objective is not to 'control a car with a BCI' but rather to predict the driver's intentions 11,13,14,29 .…”
Section: Introductionmentioning
confidence: 99%
“…The feasibility of performing single-trial recognition of ErrPs has been demonstrated in different paradigms and setups, including P300 spellers [7], Motor-imagery BCI [6], human-robot interaction [9], [8], and car driving [10]. Noticeably these signals, linked to cognitive monitoring processes, have also been reported to be rather stable across different recording days [11], and feedback characteristics [12], [9].…”
Section: Introductionmentioning
confidence: 99%